The Relationship between Foreign Direct Investment, Current Account and Economic Growth in Vietnam: A Framework for International Capital Flow Management - Trung Duc Nguyen; Anh Hoang Le (International Journal of Supply Chain Management, 2021)
The relationship between foreign direct investment (FDI), current account, and economic growth is a subject that always attracts the attention of researchers with studies that focus on both developed and developing countries. Many studies have shown that FDI has a positive effect on the growth of countries. However, this capital also brings some risks. Therefore, this study evaluates the relationship between foreign direct investment, current account, and economic growth in Vietnam. Using the VECM method combined with the Bayesian stability test, the research results have shown that, in both the short and long term, FDI and current accounts positively affect Vietnam’s economic growth. Based on research results, we propose policy implications to minimize the negative effects of FDI inflows and make the most of this capital source for the sustainable economic development of Vietnam.